IgG4-Related Intracranial Hypertrophic Pachymeningitis : A Case Report and Review of the Literature - Takeuchi, Satoru (The Korean Neurosurgical Society, 2014)
Hypertrophic pachymeningitis is an uncommon disorder that causes a localized or diffuse thickening of the dura mater. Recently, the possibility that IgG4-related sclerosing disease may underlie some cases of intracranial hypertrophic pachymeningitis has been suggested. We herein report the tenth case of IgG4-related intracranial hypertrophic pachymeningitis and review the previous literature. A 45-year-old male presented with left-sided focal seizures with generalization. Magnetic resonance imaging (MRI) revealed a diffuse thickening and enhancement of the right convexity dura matter and falx with focal nodularity. The surgically resected specimens exhibited the proliferation of fibroblast-like spindle cells and an infiltration of mononuclear cells, including predominantly plasma cells. The ratio of IgG4-positive plasma cells to the overall IgG-positive cells was 45% in the area containing the highest infiltration of plasma cells. On the basis of the above findings, IgG4-related sclerosing disease arising from the dura mater was suspected. IgG4-related sclerosing disease should be added to the pachymeningitis spectrum.